2013
DOI: 10.1039/c3ay40473k
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell force spectroscopy of Als-mediated fungal adhesion

Abstract: Macroscopic assays that are traditionally used to investigate the adhesion behaviour of microbial cells provide averaged information obtained on large populations of cells and do not measure the fundamental forces driving single-cell adhesion. Here, we use single-cell force spectroscopy (SCFS) to quantify the specific and non-specific forces engaged in the adhesion of the human fungal pathogen Candida albicans. Saccharomyces cerevisiae cells expressing the C. albicans adhesion protein Als5p were attached on at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…Our study of activation of aggregation in cell suspensions reinforces the idea that force alone is sufficient to induce surface nanodomains [ 4 , 7 , 24 ]. This remarkable activity takes place on cell surfaces without need for a signaling or metabolic response in the cell [ 4 , 5 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our study of activation of aggregation in cell suspensions reinforces the idea that force alone is sufficient to induce surface nanodomains [ 4 , 7 , 24 ]. This remarkable activity takes place on cell surfaces without need for a signaling or metabolic response in the cell [ 4 , 5 ].…”
Section: Discussionsupporting
confidence: 84%
“…First, the amyloid sequence-containing T domain in Als5p WT is only marginally stable, and the domain unfolds in response to extension forces [ 5 , 7 ]. Domain unfolding exposes the amyloid core sequence, which in turn interacts with amyloid sequences in nearby Als adhesin molecules to form cell surface nanodomains within minutes [ 4 6 , 24 26 ]. These nanodomains consist of arrayed adhesin molecules, aggregated on the cell surface through amyloid-like interactions of the amino acids in amyloid core sequences [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As further discussed in this section, we hypothesize that such interaction between Ag43α is faster and weaker than the trans-interaction detected under low pulling rate conditions. In literature, it is reported that some proteins (Als5p adhesin from C. albicans 59,60 , Nectin proteins 61 ) may associate side-by-side in cis-configuration. If adopting such a configuration for Ag43α dimers where the bends of the L-shaped proteins are in opposite direction (Figure 9a) and further considering the sole unfolding of one out of the two interacting molecules, it can be estimated that the maximal extension expected should be around 105 nm (corresponding to 292 amino-acids).…”
Section: Since Molecular Extension Above 38 Nm Cannot Results From Strmentioning
confidence: 99%
“…41,42 Briefly, triangular shaped tipless cantilevers (NP-O10, Microlevers, Bruker Corporation) were immersed for 1 h in a 10 mM Tris Buffer solution ( pH 8.5) containing 4 mg mL −1 dopamine hydrochloride (99%, Sigma), and dried with N 2 flow. Cell probes were prepared with a protocol that uses a bioinspired polydopamine wet adhesive.…”
Section: Fungal Cell Immobilizationmentioning
confidence: 99%